Penerapan Laporan Keuangan Berdasarkan ISAK 35 pada Pondok Pesantren Darussolihin Labuhan Batu - Anshari, Khairil; Ritonga, Rini Antika; Yurmaini, Yurmaini; Erliyanti, Erliyanti; Dharma, Yulius (Al-Sharf: Jurnal Ekonomi Islam, 2023)
The purpose of this research is to; (1) To increase understanding in the preparation of Financial Statements in accordance with generally accepted standards, (2) Provide knowledge about how to prepare Financial Statements of Islamic Boarding Schools based on information system technology in accordance with ISAK 35. This research uses qualitative methods, and the research approach is phenomenology. The paradigm used is a type of interpretive paradigm with three concepts, namely interpretation, meaning and understanding. Data collection techniques were conducted through unstructured interviews, passive participant observation, and documentation. Data analysis uses data reduction, data presentation, and conclusion drawing. Based on research that has been carried out at the Darussolihin Labuhan Batu Islamic boarding school, it can be seen that: (1) There is still a lack of experts in the preparation of general standard financial statements (2) The Finance Section at the Darussolihin Labuhan Batu Islamic Boarding School is not given training in the preparation of financial statements in accordance with ISAK 35 so that the financial statements prepared still apply general standards only.